Basic Engineering Science - A Systems, Accounting, and Modeling Approach - Richards, Donald E. (Open textbook library., 2001)
This textbook is based on a different paradigm for organizing an engineering science core --- a systems, accounting and modeling approach --- that emphasizes the common, underlying concepts of engineering science. Although this approach is not new, as most graduate students have been struck by this idea sometime during their graduate education, its use as the organizing principle for an undergraduate curriculum is new. By focusing on the underlying concepts and stressing the similarities between subjects that are often perceived by students (and taught by faculty) as unconnected topics, this approach provides engineering students a foundational framework for recognizing and building connections as they travel through their education.